Peran Pendidikan Berbasis Literasi Teknologi Informasi & Komunikasi dalam Memajukan SDM di Era Society 5. 0 - Helmi Said; Purnamawati; Abdul Muis Mappalotteng (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to: (1) The contribution of career guidance to job readiness in SMKN 1 Enrekang students; (2) The contribution of industrial work practice experience to the job readiness of SMKN 1 Enrekang students; (3) Contribution of career guidance and experience of industrial work practices to job readiness in SMKN 1 Enrekang students. This type of research is quantitative descriptive research, analyzing data systematically using simple regression analysis, and multiple regression analysis. Data collection techniques are interviews and questionnaires. Based on the results of data analysis, the career guidance variable has an influence of 12.96% on job readiness, the industrial work practice variable has an influence of 4.88% on job readiness, the magnitude of Adjusted R² is 0.336. This means that 33.6% of job readiness variables can be explained by independent variables, namely career guidance, work motivation, and industrial work practices